The Influence of Muzzaki Beliefs on Philantropic Manangement in Mustahik Economic Empowerment at BAZNAS Makassar - Nurhaerati; Muhammad Najib Kasim; Syahidah Rahmah (www.amertainstitute.com, 2024)
This research aims to analyze the influence of muzakki beliefs on the management of philanthropy in empowering the mustahik economy at the Makassar National Zakat Amil Agency (BAZNAS). Muzakki's trust in the institutions that manage zakat, infaq and alms plays an important role in the success of the mustahik economic empowerment program, namely people who have the right to receive philanthropic benefits. This research uses a quantitative approach with a survey method involving muzakki as the main respondent. Data was collected through a questionnaire distributed to muzakki who participated in the Makassar BAZNAS program. The research results show that there is a significant positive relationship between the level of muzakki's trust in transparency, accountability and effectiveness in managing philanthropic funds and the success of mustahik economic empowerment. Muzakki's trust not only influences the amount of donations given, but also plays a role in encouraging active participation of muzakki in economic empowerment programs. This research is expected to provide insight for zakat managers and other philanthropic institutions in increasing the trust of muzakki to maximize the impact of economic empowerment for mustahik.